Characterization of Water Kefir from Broccoli Stem Extract with Addition of Palm Sugar - Nugroho, Arhadianto Adi; Christina, Felicia; Buschle-Diller, Gisela; Purwanto, Maria Goretti Marianti; Erawati, Christina Mumpuni; Dewi, Ardhia Deasy Rosita; Mukti, Yayon Pamula; Sukweenadhi, Johan (Fakultas Farmasi, Universitas Surabaya, 2022)
Water kefir is a fermented carbonated beverage and functional food with probiotic properties. Broccoli is an edible green plant which a rich source of vitamins A, B1, B2, B3, and C; it also contains isothiocyanate compounds that have anti-cancer and fiber for digestive system. Palm sugar is a sweetener obtained from concentrated coconut sap and is known to have a low glycaemic index. The purpose of this study was to investigate the effect of broccoli stem extract and palm sugar concentration on its biochemical and microbiological characteristics. Subsequently, the acceptance of the product by the panelists were evaluated through organoleptic tests. Water kefir with sugar content of 15% had the highest lactic acid, antioxidant activity, lactic acid bacteria, yeast, ethanol content, and water kefir with a concentration of 1:5 and sugar content of 15% found the highest acceptance by the panelists. Water kefir obtained in this study did not have contaminant bacteria. This product also met the codex standard.